2011
DOI: 10.1245/s10434-011-1808-y
|View full text |Cite
|
Sign up to set email alerts
|

Needle Versus Excisional Biopsy for Noninvasive and Invasive Breast Cancer: Report from the National Cancer Data Base, 2003–2008

Abstract: The use of needle biopsy is increasing. Tumor stage, hospital volume, and hospital location were the most statistically significant predictors of biopsy type. Rates of needle biopsy at high-volume hospitals suggest that appropriate utilization of this preferred diagnostic method should approach 90%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Although accredited centers are required to have a navigation process, at least 50% of biopsies are performed outside these centers, and women are more likely to receive fragmented care (RobinsonWhite et al, 2010;Williams et al, 2011). In these settings, the following would be a common scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Although accredited centers are required to have a navigation process, at least 50% of biopsies are performed outside these centers, and women are more likely to receive fragmented care (RobinsonWhite et al, 2010;Williams et al, 2011). In these settings, the following would be a common scenario.…”
Section: Discussionmentioning
confidence: 99%
“…During this same period, the increased percentage of non-normal mammograms is unlikely to be attributable to greater use of mammography because mammography use was nearly universal (>90%) among women in the high-risk age groups (>50 years). The decrease in lumpectomies may have been attributed to the increase in use of needle biopsies (Williams et al, 2011; Zimmerman et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The large number of cases allows for robust evaluation of practice and outcomes in common cancers and for the study of rare cancers with numbers of cases that are often an order of magnitude greater than institution-based series. [9][10][11][12][13][14][15] The NCDB may also be used to study disparities and to direct policy. One study conducted by the American Cancer Society demonstrated that patients who lacked health insurance had a poorer outcome with any stage of cancer compared with patients with private insurance.…”
Section: Use Of the Ncdb For Evaluation Of Quality Of Carementioning
confidence: 99%
“…One study conducted by the American Cancer Society demonstrated that patients who lacked health insurance had a poorer outcome with any stage of cancer compared with patients with private insurance. 10,11,16,17 A bibliography of the more than 350 NCDB publications is at http://www.facs.org/ cancer/ncdb/biblclin.html. Although the NCDB was only available to a limited number of trained researchers in the past, the CoC recently established a participant user file that allows any investigator at a CoC-accredited program to conduct research using the NCDB.…”
Section: Use Of the Ncdb For Evaluation Of Quality Of Carementioning
confidence: 99%